The Implementation of Role Playing in Improving Students’ Speaking Skill in Class VI Indonesian Learning at Elementary School of Muhammadiyah 1 Sorong - Krisnawati, Reni -; Sofian Hadi, Muhamad; Tang, Ambo (Universitas Muhammadiyah Makassar, 2025)
This research aims to determine the application, effectiveness, and supporting and inhibiting factors of using the role playing method in improving students' speaking skills in Indonesian language learning in class VI at Muhammadiyah 1 Elementary School, Sorong City. The method used is a descriptive qualitative approach with a focus on in-depth understanding of the learning process. Data was obtained through observation, interviews and documentation. The research results show that the application of the role playing method is carried out through systematic stages: introduction, core activities (distribution of scenarios and roles, acting, discussion, evaluation), and closing (conclusion and reflection). This method has proven to be effective in improving students' speaking skills, which can be seen from increasing speaking fluency, vocabulary diversity, and active participation in learning. The learning atmosphere becomes more enjoyable and encourages students to dare to communicate. Factors supporting the success of this method include teacher creativity and student enthusiasm, while the main challenge is the teacher's readiness to design and guide the implementation of role playing optimally. Thus, the role playing method can be used as an innovative and effective alternative Indonesian language learning strategy.